2004
DOI: 10.1128/jb.186.2.556-565.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Rickettsia prowazekii Madrid E and Breinl Strains

Abstract: Rickettsia prowazekii, the causative agent of epidemic typhus, has been responsible for millions of human deaths. Madrid E is an attenuated strain of R. prowazekii, while Breinl is a virulent strain. The genomic DNA sequence of Madrid E has recently been published. To study the genomic variations between Madrid E (reference) and Breinl (test) DNAs, cohybridization experiments were performed on a DNA microarray containing all 834 protein-coding genes of Madrid E. Of the 834 genes assessed, 24 genes showed 1.5-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Zhu et al, using intergenic spacers rpmE/tRNAfMet and serS/virB4, differentiated 5 strains and PCR amplicons from 10 body lice of R. prowazekii into 4 genotypes (12). Ge et al showed that R. prowazekii Breinl strain and E strain were different in the rp084 gene, which was deleted from the Breinl strain (13). However, using the rpmE/ tRNAfMet intergenic spacer, we were able to classify the 8 strains of R. prowazekii tested into only 2 genotypes.…”
Section: Discussionmentioning
confidence: 81%
“…Zhu et al, using intergenic spacers rpmE/tRNAfMet and serS/virB4, differentiated 5 strains and PCR amplicons from 10 body lice of R. prowazekii into 4 genotypes (12). Ge et al showed that R. prowazekii Breinl strain and E strain were different in the rp084 gene, which was deleted from the Breinl strain (13). However, using the rpmE/ tRNAfMet intergenic spacer, we were able to classify the 8 strains of R. prowazekii tested into only 2 genotypes.…”
Section: Discussionmentioning
confidence: 81%
“…Like the genomic contents of other intracellular bacteria (3,16,17,19), the genomic contents were found to be fairly conserved among E. chaffeensis strains. Thus, this type of microarray is more suitable than a gene content-based microarray for discerning diversity among E. chaffeensis strains.…”
Section: Discussionmentioning
confidence: 81%
“…Although the status of COX isozymes in EC infected with typhus rickettsiae is currently under investigation, evidence derived from the presented data and earlier observations (48,50) suggest significant increases in the production of the major endothelial prostaglandins PGE 2 and PGI 2 during infection and implicate COX-2 and its reaction metabolites as having an integral role in the pathophysiology of rickettsial diseases. In this context, comparative studies with highly pathogenic versus avirulent species of SFG rickettsiae or with individual strains with various degrees of virulence, for example, R. rickettsii isolates that have been characterized for their ability to cause oxidative stress in EA.hy 926 endothelial cells (16) or R. prowazekii strains at opposing ends of the virulence spectrum (19), to define potential differences in the intensity and kinetics of COX-2-mediated host responses will yield important new information about virulence determinants and pathogenic mechanisms. While our initial studies suggested that in vitro infections of endothelial cells with the virulent Sheila Smith and avirulent Iowa B strains trigger COX-2 mRNA and protein expression (E. Rydkina and S. K. Sahni, unpublished observations), a detailed investigation of the correlation between the extent of infection, host cell response, and cytopathic potential of different rickettsial species and strains is currently in progress.…”
Section: Discussionmentioning
confidence: 99%